A Survey on HealthBot using Machine Learning Algorithms - Sathya, N; Jayendren, S; Prasanth, S; Sharmila, S (International Journal of Computer Sciences and Engineering, 2019)
Nowadays, People care a lot about their health. Similarly, they have a pocket rocket technical object, which depicts the technological updating of the well beings. There is an application called HealthBot. HealthBot is a computer program planned to re-enact discussion with human clients to procure information approximately his wellbeing status, especially over the Internet. The Wellbeing Bot Benefit could be a SaaS arrangement that engages its accomplices to construct and send compliant, AI-powered wellbeing operators, permitting them to offer their clients brilliantly, personalized get to health-related data and intuitive through a normal discussion encounter. So, on considering the people’s priority list, an application that takes care of one’s health with the help of that technology was considered into account. As an account of such consideration, Rovi 1.0 is born from the three Budding Software engineers. At present, we have such things but this rovi will stand out in many aspects. The main scope & objective of this is to act like a packet nurse. To suggest the medicine for the diseases. It includes the most efficient way of maintaining the report that is useful in any situation. It includes the main supervised learning process that is more efficient. Prevention is better than cure. Systems are needed for dynamic interaction with people to gather Information, Monitor health condition and provide support, especially after hospital discharge or at-home settings. This can be possible by using the healthbot technique. This paper highlights different Information Mining strategies such as classification, clustering, affiliation conjointly highlights related work to dissect and foresee human illness.